Detection of Multidrug-Resistant (MDR) Escherichia coli Isolated from Raw Milk in East Java Province, Indonesia - Ribby Ansharieta1 , Mustofa Helmi Effendi2,3, Hani Plumeriastuti4 (Institute of Medico-legal Publications Pvt Ltd, 2020)
The aim of this study is to figure out the profile of antibiotic resistance in E. coli, sourced from raw milk,obtained from five districts in East Java Province, Indonesia. A total of 250 samples were tested usingthe Kirby-Bauer Test method. The result revealed that the highest percentage of antibiotic resistance wasTetracycline (17.05%), followed by Streptomycin (14.2%), Trimethoprim (9.66%), Chloramphenicol(7.95%) and Aztreonam (1.7%). A total of 16 E. coli isolates (9.1%) were detected as MDR, and 3 E. coliisolates (1.7%) were suspected as presumptive ESBL. Thus, threat of multidrug resistance E. coli possiblysourced from the milk.